Socio-Economic Disclosure in Islamic Banking Case Study in Indonesia - Atina Shofawati (Global Review of Islamic Economics and Business, 2014)
Islamic Banking must give benefit for their stakeholders. Benefit reflects the performance of Islamic Banking which can be seen through their annual reports. One of important information which reflects the performance of Islamic Banking is socio-economicdisclosure. This report gives information about the performance of Islamic Banking which covers social and economic aspects which show the social economic responsibility of Islamic Banking. Socio-economic disclosure indicators have been taken from Corporate Social Performance which are the indicators consist of four parts, namely community involvement; human resources; natural resources and contribution to the environment; contribution to the product or service. This paper uses qualitative method. This research identifies the socioeconomic disclosure from annual report of Islamic Banking in Indonesia, majoring Bank Syariah Mandiri and Bank Muamalat Indonesia. The result of this paper shows that Bank Syariah Mandiri and Bank Muamalat Indonesia conduct social economic responsibility through socio-economic disclosure from annual report of both of the Islamic Banks in 2009.